Risk factors and prediction score model for unplanned readmission among neonates with NRDS under one year of age: A retrospective cohort study - Weihong, Yue; Hong, Wei; Feng, Chen; Xinhong, Chen; Zhen‑E, Xu; YA, HU (Frontiers in Pediatrics, 2022)
Objective: To analyse the risk factors and establish a prediction score model for unplanned readmission among neonates with neonatal respiratory distress syndrome (NRDS) for respiratory problems under one year of age. Methods: This retrospective cohort study enrolled 230 neonates with NRDS who were admitted between January 2020 and December 2020. The infants were classified into two subgroups based on whether they were readmitted for respiratory problems under one year of age: Readmit group and Non-readmit group. Readmission risk factors for NRDS were analysed by logistic regression and a prediction score model was generated. Results: Among the 230 enrolled infants, 51 (22%) were readmitted, and 179 (78%) were not readmitted. In univariate analysis, compared with Non-readmit group infants, Readmit group infants had a significantly younger birth gestational age (31.9±2.3 vs 32.8±2.5 weeks, p=0.012), lower birth weight (BW) (1713.7±501.3 g vs 1946.8±634.4 g, p=0.007), older age at discharge (41.7 vs 31.7 days, p=0.012), higher proportion of NEC (31% vs 16%, p=0.016), higher rate of blood transfusion (39% vs 25%, p=0.049), higher rate of postnatal dexamethasone administration (28% vs 9.5%, p=0.001), and higher rate of home oxygen therapy (HOT) (57% vs 34%, p=0.003). Moreover, Readmit group infants had a significantly longer antibiotic days usage (12.0 vs 10.0 days, p=0.026) and a longer duration of hospital stay (41.0 vs 31.0 days, p=0.012) than Non- readmit group infants. The multivariate logistic regression analysis showed that taking readmission as a target variable, postnatal DEX administration (OR 2.689, 95%CI 1.168 to 6.189, p=0.020), HOT (OR 2.071, 95%CI 1.060 to 4.046, p=0.033) and NEC (OR 2.088, 95% CI 0.995 to 4.380, p=0.051) could be regarded as risk factors for readmission. A score model predicting readmission was administered with a positive predictive value of 0.651 (95% CI: 0.557 to 0.745, p=0.002), with a sensitivity of 0.412 and a specificity of 0.888 at a cut-off of 3.5 point, which were evaluated on the ROC curve. Conclusions: Postnatal DEX administration, HOT and NEC were risk factors for readmission of NRDS. NRDS infants with a predictive score of 3.5 point or more were at a high risk for unplanned readmit.